Darwinism as religion: what literature tells us about evolution - Ruse, Michael (Oxford University Press, 2017)
Prologue -- The eighteenth century -- Before Darwin -- The Darwinian theory -- Reception -- God -- Origins -- Humans -- Race and class -- Morality -- Sex -- Sin and redemption -- The future -- Towards the present -- The conflict continues -- Epilogue